LEGAL PROTECTION FOR HUMAN TRAFFICKING: A Case Study of Sidoarjo District Court Decision No. 889/PID.SUS/2018/PN.SDA - Rahmawati, Shofi Nurul; Sumaryanto, Djoko (YURIS: Journal of Court and Justice, 2022)
The objective of this research is to determine the regulation of the human trafficking crime and analyze of the human trafficking crime in Decision No. 889/PID.SUS/2018/PN.SDA. A criminal act or "strafbaar feit" is an act which regulated by law that is prohibited and punishable by crime. It means that this act can be an active act (doing something that is actually prohibited by law) or a passive act (not doing something that is actually required by law). The method used in this research is juridical normative method. Legal material source used in this research was library research. It conducted by reading, analyzing, studying, and identifying legal materials that are appropriate with the topic of this research, then implemented into this research. Legal material sources obtained from primary legal materials and secondary legal materials. Selecting appropriate legal materials aims to complete understanding of human trafficking crime. The legal material will be processed and analyzed quantitatively in order to explain the statement problems that are closely related to this research. The researchers can conclude that the act of a husband selling his wife to engage in deviant sex (threesome) still cannot be considered a criminal act of human trafficking. Based on the case described, before imposing sanctions, the judge must be more thorough and careful in implementing the law and pay attention to the conscience of the victim in order to realize the court as an institution that provides a sense of justice.